Congenital aniridia: clinical profile of children seen at the University College Hospital, Ibadan, South-West Nigeria (2021)
Purpose: To describe the clinical features of patients younger than 16 years with aniridia presenting to the Paediatric Ophthalmology unit of the Eye Clinic, University College Hospital, Ibadan, Nigeria. Methods: The is a retrospective review of children with aniridia seen between May 2015 and April 2019 at the Paediatric Ophthalmology unit of the Eye Clinic, University College Hospital in Ibadan. Data on demographic characteristics, presenting complaints, ocular and systemic examination findings, and interventions were collected and descriptively summarised. Results: A total of 28 eyes of 14 patients were studied. The mean age was 6.37 ± 4.98 years. Seven (50%) patients were male. Aniridia was diagnosed in first-degree relatives of nine patients. The most common complaint at presentation was poor vision in 11 (78.6%) patients. Objective visual acuity assessment was obtained in 22 (78.6%) eyes. Presenting visual acuity was worse than 20/60 in all 22 eyes and worse than 20/400 in 8 (36.4%) eyes. Refraction was performed in 17 (60.7%) eyes and revealed a mean spherical equivalent of −3.93 ± 5.99 diopters. Twenty (71.4%) eyes had corneal opacities, and lenticular opacities were seen in 15 (62.5%) of 24 eyes. Mean intraocular pressure (IOP) at presentation was 21.62 ± 10.4 mmHg; 12 (41.4%) eyes had elevated IOP at presentation. Ten (35.7%) eyes had cataract surgery and six (21.4%) eyes had glaucoma surgery. Conclusion: Familial aniridia was common in this study, and most of the patients presented with moderate to severe visual impairment. The common ocular associations were refractive error, cataract, corneal opacity and glaucoma.